Predictive value of three-dimensional echocardiographic variables on development of myxomatous mitral valve disease in dogs - Isaksson, Moa (SLU/Dept. of Clinical Sciences (until 231231), 2022)
Myxomatous mitral valve disease (MMVD) is the most common acquired cardiovascular disease and the most common cause of congestive heart failure (CHF) in dogs. Cavalier King Charles Spaniels (CKCS) is one of the breeds most commonly affected by MMVD and disease progression has been shown to occur at a younger age among CKCS, when compared to other breeds. The age of onset of MMVD is an inherited trait among CKCS and the geometry of the mitral valve has recently become of interest among veterinary researchers to obtain deeper understanding of the currently partly understood pathogenesis. Findings suggest that dogs with MMVD and many healthy CKCS share an altered three-dimensional (3D) geometry of the mitral valve annulus, which differs from healthy dogs of other investigated breeds. In this comparison, the mitral valve annulus has been shown to lack the normal saddle-shaped appearance, instead it had a flattened appearance among many of the healthy CKCS and dogs with MMVD. This flattening has been proposed as a factor contributing to the early onset of disease progression in CKCS. The object of this thesis was to evaluate whether a flattening of the mitral valve (MV) in healthy dogs might contribute to an accelerated progression of MMVD. It was hypothesized that MV variables indicative of flattening, when measured with real-time 3D transthoracic echocardiography (RT3D-TTE), might be used as a prognostic test to determine dogs at risk for progression of early onset or severe MMVD. The study was conducted as a follow-up of dogs with preexisting RT3D-TTE datasets, obtained 6 years earlier during an initial study that aimed to describe morphological mitral valve variations between healthy CKCS and non-CKCS. The present study included a follow-up questionnaire, distributed to and returned by owners of dogs with preexisting RT3D-TTE datasets, designed to evaluate cause of death (cardiac/non-cardiac) and possible progression to congestive heart failure (CHF) for deceased dogs. The questionnaire also facilitated staging of disease severity among dogs still alive, and owners of alive dogs were invited for a follow-up examination; including auscultation and new standard echocardiographic examination, as well as new RT3D-TTE examination. The following RT3D-TTE MV variables; annulus height (AnH), normalized tenting volume (nTnV), tenting area (TnA) and tenting height (TnH) - proposed to be representative of a flattened appearance of the MV annulus - were measured in datasets from the initial study and compared to the dogs' disease stage at follow-up. Information was received from a total of 24 dogs (n=18 CKCS and n=6 non-CKCS) from the initial cohort of 29 healthy dogs, 62.5% of these dogs were reported by owners as still alive at time of follow up. Deceased dogs made up 37.5% of the studied population (n=6 CKCS and n=3 nonCKCS). None of the owners of deceased dogs reported cardiac-related deaths, and only one of the deceased CKCS was reported by the owner as having progressed to CHF pre-mortem. The mean age at follow-up for the CKCS (alive and deceased) was 8.6 years [SD 0.43] and among all the CKCS, 56% had developed a heart murmur discovered by a veterinarian at a mean age of 7.8 years [SD 2.6]. Three dogs; n=2 CKCS and n=1 non-CKCS, had progressed to stage B2, i.e. MMVD and signs of volume overload. These dogs had presented with a pronounced flattening of the mitral valve annulus at initial study, as they aggregated at the lower numerical range regarding all four variables. In conclusion, this particular cohort of dogs were represented by mainly preclinical cases of MMVD, with the exception of one CKCS that had progressed to CHF pre-mortem. Three dogs that had presented with a flattened mitral valve annulus at the initial study, tended to have progressed to MMVD with echocardiographic signs of left sided volume overload at follow-up.